MtDNA species-level phylogeny and delimitation support significantly underestimated diversity and endemism in the largest Neotropical cichlid genus (Cichlidae: Crenicichla) - Oldřich Říčan (PeerJ Inc., 2021)
Crenicichla is the largest and most widely distributed genus of Neotropical cichlids. Here, we analyze a mtDNA dataset comprising 681 specimens (including Teleocichla, a putative ingroup of Crenicichla) and 77 out of 105 presently recognized valid species (plus 10 out of 36 nominal synonyms plus over 50 putatively new species) from 129 locations in 31 major river drainages throughout the whole distribution of the genus in South America. Based on these data we make an inventory of diversity and highlight taxa and biogeographic areas worthy of further sampling effort and conservation protection. Using three methods of molecular species delimitation, we find between 126 and 168 species-like clusters, i.e., an average increase of species diversity of 65–121% with a range of increase between species groups. The increase ranges from 0% in the Missioneira and Macrophthama groups, through 25–40% (Lacustris group), 50–87% (Reticulata group, Teleocichla), 68–168% (Saxatilis group), 125–200% (Wallacii group), and 158–241% in the Lugubris group. We found a high degree of congruence between clusters derived from the three used methods of species delimitation. Overall, our results recognize substantially underestimated diversity in Crenicichla including Teleocichla. Most of the newly delimited putative species are from the Amazon-Orinoco-Guiana (AOG) core area (Greater Amazonia) of the Neotropical region, especially from the Brazilian and Guiana shield areas of which the former is under the largest threat and largest degree of environmental degradation of all the Amazon.